IDDF2020-ABS-0201 Targeting hepatoma-intrinsic pparγ signaling overcomes immune checkpoint therapy resistance by inflaming the tumor microenvironment. (18th November 2020) - Xiong, Zhewen; Chan, Stephen; Zhou, Jingying; Cao, Jianquan; Vong, Joaquim SL; Zeng, Xuezhen; Tu, Yalin; Feng, Yu; Yip, Kevin; Sung, Joseph JY; Cheng, Alfred Sze-Lok
Abstract : Background: Immune-checkpoint blockade (ICB) therapies by antibodies against programmed death 1 (PD1)/PD1 ligand 1 (PD-L1) axis have revolutionized the treatment paradigm for cancer. Although subsets of people exhibit durable responses, ICB resistance has increasingly been observed, especially in hepatocellular carcinoma (HCC). Here we utilized a single-cell RNA-sequencing (scRNA-seq) approach to elucidate the tumor-intrinsic mechanism underlying tumor immunosuppression and ICB resistance. Methods: We first recapitulated the clinical outcome of ICB resistance via repeated cycles of in vivo selection in orthotopic murine models of HCC. To investigate the tumor cell-extrinsic resistant factors, the myeloid and lymphoid immune populations were profiled by multi-color flow cytometry. To dissect hepatoma-intrinsic resistant signatures, we performed scRNA-seq from anti-PD-L1-treated tumors generated from parental or PD-L1R Hepa1-6 cells. The anti-tumor efficacy and immunophenotype of combined therapy with anti-PD-L1 antibody and peroxisome proliferator-activated receptor gamma (PPARγ) antagonist T0070907 were further determined. To demonstrate the clinical relevance of PPARγ, we performed scRNA-seq analysis of tumor biopsies from advanced HCC patients who received anti-PD-1 treatment. Results: We successfully established anti-PD-L1-resistance models, which were accompanied with lower CD8 + T cells and T helper 1 (TH 1) cells but higher exhausted T cells and myeloid-derived suppressor cells (MDSCs). Integrative gene expression analysis showed significant enrichment of PPARγ signaling in PD-L1R tumor cells. Importantly, T0070907 overcame ICB resistance in HCC, which was accompanied with enhanced cytolytic activity and reduced T cell exhaustion and decreased infiltration of MDSCs. Notably, scRNA-seq profiles of human biopsies uncovered adaptive upregulation of tumor-cell intrinsic PPARγ and re-shaping of T cell exhaustion in non-responders upon anti-PD-1 therapy. Conclusions: Taken together, hepatoma-intrinsic PPARγ activation might be associated with immune evasion and ICB resistance. Pharmacological inhibition of PPARγ sensitized tumors to anti-PD-L1 therapy, thus representing a promising strategy to overcome ICB resistance.